What is more effective in building a person’s character: encouragement or criticism? (Journal of Parents and Teachers, 2026)
The process of personal growth and development is a delicate one, and there may be factors that either help or hinder it. This article focuses on the question of what is most helpful: encouragement or criticism, whether at home or at school; naturally, criticism should never be delivered in a dismissive or angry manner. Different types of criticism are suggested, whether offered beforehand to prevent certain behaviour, or afterwards to prevent it from recurring. Finally, some activities are suggested as exercises in offering constructive criticism in specific situations.
Keywords: to encourage; to criticise; to help someone develop as a person